FREUD’S VIEW ON THE ORIGIN OF RELIGION AND ITS CRITICISM ACCORDING TO ‘AQL AND NAQL - Hosseini Eskandian, Abdullah; Babaei, Ali (Ulul Albab: Jurnal Studi Islam, 2023)
The origin of religion remains a central and contested issue in the philosophy of religion and modern theology (kâlâm), frequently drawing skepticism from materialist and atheist perspectives. This foundational question shapes the identity of religion and determines whether it is viewed as divinely revealed or as a construct of human imagination and psychological needs. Theistic scholars assert that religion originates from a divine source, revealed through Prophets for the moral and spiritual guidance of humanity. In contrast, materialists and atheists, including prominent figures such as Sigmund Freud (1856–1939), argue that religion emerges from human psychological complexes, instincts, and social conditioning, denying any transcendent origin. Freud, in particular, attributes the genesis of religion to repressed desires and unresolved familial tensions, especially within the context of totemism and the Oedipus complex, thus rejecting any metaphysical or divine foundation. This article employs a descriptive-argumentative method and an analytical approach to examine and critically assess Freud’s theory on the origin of religion. The study highlights several conceptual and methodological flaws in Freud’s view, including the inadequacy of instinctual explanations for religious consciousness, the problematic generalization of Christian-specific myths, the irrationality of totemic belief systems, and the ethnocentric limitations of his framework. Furthermore, Freud’s theory stands in direct contradiction to key Islamic theological principles rooted in reason (ʿaql) and inspired revelation (naql), particularly as conveyed through the Qur’an and Hadith. Ultimately, this critique underscores the incompatibility of Freud’s reductionist account with both Islamic epistemology and the innate disposition of human spirituality (fitrah).